The reliability of accelerometry to measure weightlifting performance - Sato, K.; Sands, W. A.; Stone, M. H. (Sports Biomechanics, 2012)
The purposes of the study were to track weightlifters' barbell acceleration with a portable accelerometer over three training sessions to examine test-retest reliability and to compare peak barbell acceleration at different training intensities. Twelve nationally ranked weightlifters volunteered for this study. The portable accelerometer was attached to the right side of the barbell to measure barbell resultant acceleration during the snatch lift at a sampling frequency of 100 Hz. The data were collected over three training sessions at intensity levels of 80%, 85%, and 90% of one repetition maximum. The data were analyzed using intra-class correlation coefficients (ICCs) for the three training sessions and oneway repeated measure ANOVA to compare the difference in peak barbell acceleration at three intensities. Results showed that the device was highly reliable with an ICC of 0.88 and 95% confidence interval of 0.81-0.93. There were significant differences in peak barbell acceleration at various lifting intensities, indicating a decline of the acceleration as the mass of the barbell became heavier. The portable accelerometer seems useful in measuring barbell acceleration data, which can be analyzed in future studies to monitor a weightlifter's performance in a practical setting instead of testing at a laboratory.